THE IMPLEMENTATION PROCESS OF ROCK MINING LICENSING IN BREBES REGENCY - Wati, Liana; Sulandari, Susi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
Liquid Rock Mining is one of the business activities by utilizing the existing mineral resources. Unfortunately, there are many rock mining activities are carried out without permission or illegal, thus giving rise to various literature nowadays. This research aims to analyze the implementation of the rock mining licensing policy in Brebes District and to know the supporting factors and the inhibiting factor which influence it. Data retrieval is conducted through interviews with informants chosen in purposive. Data analysis is filed with the triangulation method. The results showed that rock clearance in Brebes is registered in accordance with the governor's regulation number 18 the year 2016 about the implementation of energy and mineral resources in the Central Java province. However, it still encountered some constraints as a long licensing process, the management of the support document is done in several forging until the lack of human resources. This permission is also supported by the Office of the District of Slamet Utara which is closer to Brebes and permits sites that are easily obtained through the website of Dinas PMPTSP JATENG and Dinas ESDM JATENG.